Interacting With Competence: A Validation Study of the Self-Efficacy in Intercultural Communication Scale-Short Form - Kabir, Russell S.; Sponseller, Aaron C. (Frontiers in Psychology, 2020)
Self-efficacy as applied to language learning encompasses the belief in one’s ability to obtain mastery in a sought-after domain of linguistic competence by committing to goals and maintaining acquired skills. Intercultural communication and effectiveness are of interest to the professional and personal language goals of learners as their progress depends upon a strong motivation to put practical language skills to use when the real-world requires it. Studying or working abroad and engaging in intercultural training are two such contexts that bind research in learner characteristics between applied linguistics and positive psychology as they provide a substrate of concrete interactions through language brokering, transformative experiences characterized by opportunities for changes in self-concept, negotiations with values and authenticity, and forms of interpersonal development underwritten by intercultural communication as an ability. The Self-Efficacy in Intercultural Communication Scale (SEIC) was developed by Peterson et al. (2011) in a sample of educators with overseas sojourning work experience. However, the original study lacked confirmatory analyses of internal and external validity that would provide clarity toward model identification and applicability for research that deals with intercultural communication competence across populations with diverse sample characteristics. A total of 876 teachers (M age = 37.48, SD = 10.81) and 266 university students (M age = 19.48, SD = 0.74) in Japan responded to items from the SEIC instrument. Acceptable model fit was supported for the 8-item short-form as proposed by Peterson et al. (2011). Metric invariance was observed for individuals from a sample of sojourning English language teachers similar to the original validation and a nationwide survey of Japanese teachers of English, offering indications of cross-cultural validity. Degrees of equivalence were also found for the Japanese items as extending fitness for use to students from two universities in Japan. Concurrent validity was supported for self-efficacy in intercultural communication measured by the scale with intercultural effectiveness competencies and speaking and listening self-efficacy constructs used in classroom contexts. Together, this study offers a tool of valid indicators for researchers and practitioners who aim to observe this self-efficacy in positive education or programs that intersect with language learning and intercultural communication.